Proteomic analysis of pyridoxal oxime derivatives treated Listeria monocytogenes reveals down-regulation of the main virulence factor, Listeriolysin O. (May 2020) - Šrajer Gajdošik, Martina; Andjelković, Uroš; Gašo-Sokač, Dajana; Pavlović, Hrvoje; Shevchuk, Olga; Martinović, Tamara; Clifton, James; Begić, Marija; Josić, Djuro
Graphical abstract: Highlights: Pyridoxal oxime derivatives (POD) caused significant changes in bacterial proteome. Most changes in expression of key cell antigens were observed. Treatment with PODs caused significant downregulation of toxin listeriolysin O (LLO). Listeriolysin O is a potential biomarker candidate for L. monocytogenes contamination. Abstract: Proteomic analysis of foodborne pathogen Listeria monocytogenes after treatment with three disinfectants based on ammonium salts of pyridoxal oxime (POD) reveal perturbation of cellular processes. These inhibitors caused disturbance in the synthesis of plasma membrane proteins and cell wall proteoglycans. Some of key proteins and proteoglycans from these two groups that are important for bacterial growth are down-regulated. Additionally, we demonstrated that the main bacterial toxin Listeriolysin O (LLO) is significantly down-regulated after treatment with each of three investigated inhibitors. These investigations confirm already postulated mechanism of action of POD-based inhibitors that results in disturbance of key cell surface proteins and proteoglycans in Gram-positive bacteria. Additionally, the use of some proteins such as LLO, as potential biomarker candidates of food poisoning with this bacterium is discussed.